Systematic Review of the Human Milk Microbiota. (27th September 2016) - Fitzstevens, John L.; Smith, Kelsey C.; Hagadorn, James I.; Caimano, Melissa J.; Matson, Adam P.; Brownell, Elizabeth A.
Abstract : Human milk–associated microbes are among the first to colonize the infant gut and may help to shape both short‐ and long‐term infant health outcomes. We performed a systematic review to characterize the microbiota of human milk. Relevant primary studies were identified through a comprehensive search of PubMed (January 1, 1964, to June 31, 2015). Included studies were conducted among healthy mothers, were written in English, identified bacteria in human milk, used culture‐independent methods, and reported primary results at the genus level. Twelve studies satisfied inclusion criteria. All varied in geographic location and human milk collection/storage/analytic methods. Streptococcus was identified in human milk samples in 11 studies (91.6%) and Staphylococcus in 10 (83.3%); both were predominant genera in 6 (50%). Eight of the 12 studies used conventional ribosomal RNA (rRNA) polymerase chain reaction (PCR), of which 7 (87.5%) identified Streptococcus and 6 (80%) identified Staphylococcus as present. Of these 8 studies, 2 (25%) identified Streptococcus and Staphylococcus as predominant genera. Four of the 12 studies used next‐generation sequencing (NGS), all of which identified Streptococcus and Staphylococcus as present and predominant genera. Relative to conventional rRNA PCR, NGS is a more sensitive method to identify/quantify bacterial genera in human milk, suggesting the predominance of Streptococcus and Staphylococcus may be underestimated in studies using older methods. These genera, Streptococcus and Staphylococcus, may be universally predominant in human milk, regardless of differences in geographic location or analytic methods. Primary studies designed to evaluate the effect of these 2 genera on short‐ and long‐term infant outcomes are warranted.